NFC Implementation to Improve Business Process - Marisa Karsen (Bina Nusantara University, 2013)
Every industry needs IT to improve their business and give faster service to customer. The fast growing of social network (Facebook, Twitter, MySpace, LinkedIn) and Smartphone (Blackberry and iPhone) in Indonesia indicate that Indonesian people are already familiar with high technology and it is the right time to introduce new technology in Indonesia. The problem is, the usage of IT-based system in Indonesia is not optimal. Nowadays, people want to do almost everything faster and more convenient using technology. We know thatuntil now, there are a lot of situations that make people queue or wait to get their need. In this kind of situation, we need something that will change the way to do business, that is in effective and efficient way. NFC (Near Field Communication) is considered suitable as the solution. NFC technology as one of payment systems can increase competitive advantage of the company which implements it and will make it a leader in the industry. This new technology could attract customers, especially Indonesian people in big cities who want to do their transaction in quick and efficient way. NFC is already implemented in Korea and USA as substitution of e-wallet that can help people to make transactions easier and faster. I believe NFC can be implemented in Indonesia to make new trend of doing business.